Role curator of the academic group in the formation of a professional orientation of future mining engineers (Pedagogy of Higher and Secondary Education, 2016)
Bondarenko O. V. Role curator of the academic group in the formation of a professional orientation of future mining engineers.Relevance of the proposed article the problem range that can be represented as non educational services requirements of society demands of the individual, the needs of the labor market. The author proves that the leading role in solving the urgent problems of education belongs curator of the academic group. In the article the content of the curator of the academic group, including its functions (analytical, organizational, communication, controlling, socialization) and areas of work within five years teaching students in higher education.The author argues that curators often overlooked is this aspect as the formation of a professional orientation of future mining engineers.The purpose of the article is the characteristic forms and methods of work of the curator, directed towards professional orientation of future mining engineers.In the article the author defines the concept of «professional orientation» and «readiness for future mining engineers to the profession». The said readiness is revealed as a complex personality formation, which is found in the unity of the whole motivational, content-operational, emotional and volitional and evaluative, reflective components.Author determined the most effective forms and methods of vocational guidance in higher education (excursions, travel distance learning, training exercises, discussion) submitted their examples.
Keywords: curator; academic group; future mining engineers; professional orientation; professional work; commitment to professional activities; vocational work; forms and methods of vocational guidance of curator